Role of Acupuncture in Back Pain– Experience in the Department of Physical Medicine, CMH Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Back pain is one of the common causes of pain after headache and a major debilitation in adult. Low back pain includes dorsal pain at anywhere between 12th thoracic vertebrae and lower buttock up to gluteal folds or anus. In United States, as many as one third of the population suffer from chronic pain conditions. Acupuncture is a recommended treatment for back pain. The action of acupuncture is an analgesic and considered a valuable asset in the specialty of pain management.Objective: To evaluate the role of acupuncture on back pain and to follow up the quality of life in patients with back pain.Materials and Methods: This was a prospective experimental study and was carried out at the Department of Physical Medicine, Combined Military hospital (CMH), Dhaka Cantonment from June 2015 to December 2015. A total of twenty two patients were enrolled and were randomly selected who received conservative treatment for pain management for 4 to 6 weeks and did not get improvement. Needling was done at acu-points on average of 15 to 20 needles for a period of 15-30 minutes for three days in a week for 06 weeks. The concise assessment was done for effectiveness in pain management.Results: The result was observed in terms of the VAS (Visual analog scale) and disability scale. Relief of pain was noted to complete or to moderate in 58% of the cases. After 02 months of acupuncture treatment, 60% patients had relief of pain. After 06 months of acupuncture treatment, about 30% patients remained moderate to complete pain free.Conclusion: Acupuncture remains one of the alternative medicine disciplines and there is mounting evidence of its effectiveness. Most of the patients were benefitted with acupuncture treatment regime after failure of conservative treatment for duration of 4-6 weeks for back pain.Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 85-89